PENGGUNAAN HAK ANGKET DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA, SETELAH PERUBAHAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - David Aprizon Putra (University Of Bengkulu Law Journal, 2017)
Dewan Perwakilan Rakyat Republik Indonesia is one of the institutions of the state that has experienced the impact of the change. One line that significantly changes is on the function line. After the changes in the Undang-Undang Dasar 1945 the Dewan Perwakilan Rakyat Republik Indonesia has three functions in which the matter is mandated in article 20A (1). The three functions are legislative functions, budget functions and supervisory functions. One of the functions of supervision owned by the Dewan Perwakilan Rakyat Republik Indonesia is the inquiry right. Prior to the changes in the Second State ndang-Undang Dasar 1945, the oversight function of the Dewan Perwakilan Rakyat Republik Indonesia was only regulated in a general explanation, and this also seems very general and has not been explicitly explained. Then after the second amendment to the ndang-Undang Dasar 1945, then the inquiry right as one of the supervisory functions was more explicitly regulated, namely in Article 20A (2). The legal consequences of the use of the ndang-Undang Dasar 1945 inquiry rights to the President's policies can lead to efforts to dismiss the president and, or Vice-President, if the president's policy violates article 7A of the Undang-Undang Dasar 1945, from that the author considers this need to be understood and studied more deeply.